Relasi Kematian dan Penyempurnaan Jiwa dalam Filsafat Islam: Studi Terhadap Pemikiran Mulla Sadra - Rasid, Rasid; Sabirin, Falah (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
This study seeks to address issues surrounding death by presenting the core ideas developed by Mulla Sadra in his work al-Asfa>r and several other literatures. Some people perceive death as absolute annihilation and a frightening event to be avoided. In reality, however, death is a natural and inevitable occurrence for every living being with a soul. This indicates a misunderstanding of the terminology of death that has developed in society. Using an interpretive paradigm and the hermeneutical-interpretive method, this study finds that the essence of death has an essential relationship with the reality of the soul and its process of perfection. This study concludes that death is a logical consequence of the soul’s process of perfection. Since the soul constantly undergoes a process of refinement and is directed (al-tawajjuh) toward perfection, it must abandon materiality and all material-related aspects to achieve its ultimate state. The findings of this study provide an explanation that death is neither a terrifying event nor absolute annihilation, as commonly assumed. In reality, death is a transition from one form of existence to another. Furthermore, this study offers new insights, countering the long-held view that death is merely a result of the deterioration of temperament (miza>j) and the faculties of the soul, as proposed by Ibn Sina, materialists, and the medical field.